2022
DOI: 10.3390/vaccines11010053
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the Immune Response in Balb/c Mice after the Co-Administration of a Vector-Based COVID-19 Vaccine with Cytosine Phosphoguanine Oligodeoxynucleotide

Abstract: The effects of cytosine phosphoguanine oligodeoxynucleotides (CPG ODNs) on immune response have been demonstrated for different vaccines; however, such information is limited for the vector-based Coronavirus disease 2019 (COVID-19). This paper aims to demonstrate the potential effect of CPG ODNs on immunological response against the vector-based COVID-19 vaccine on Balb/c mice using a JNJ-78436735 Ad26.COV2-S recombinant as a model vaccine. A total of 18 BALB/c mice clustered into six groups were used. All gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…This supports the study conducted by Jurk et al 24 who showed that CpG ODNs are potent inducers of the innate immune system. Our findings also confirm those of 25 who showed that J&J vaccination against SARS-CoV-2 at low and high doses in combination with CpG ODN 18281-1, CpG ODN 18281-2, and CpG ODN 18289 generated higher levels of specific IgG than the vaccine alone. On the other hand, 26 demonstrated that the majority of antibodies were IgG2a in mice injected with HBsAg containing CpG ODN (1826), indicating a potent Th1-type response.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This supports the study conducted by Jurk et al 24 who showed that CpG ODNs are potent inducers of the innate immune system. Our findings also confirm those of 25 who showed that J&J vaccination against SARS-CoV-2 at low and high doses in combination with CpG ODN 18281-1, CpG ODN 18281-2, and CpG ODN 18289 generated higher levels of specific IgG than the vaccine alone. On the other hand, 26 demonstrated that the majority of antibodies were IgG2a in mice injected with HBsAg containing CpG ODN (1826), indicating a potent Th1-type response.…”
Section: Discussionsupporting
confidence: 92%
“…Blood biochemical profiles are a useful diagnostic tool since they show the animal's physiological condition. 25 Urea and creatinine levels were determined to check kidney function and, ALT and AST levels were also determined to check liver function in mice immunized with the vaccine + CpG ODN 2395. This study observed no significant difference in values of these parameters between the treated groups and the untreated group (p ≥ 0.05) (Figure 4).…”
Section: Discussionmentioning
confidence: 99%